Relasi Magis, Agama dan Pengetahuan dengan Sistem Kepercayaan Tradisional pada Long Storage Kalimati (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
Related to the traditional belief in the Long Storage of Kalimati, this study aims to explain the relationship between various kinds of beliefs that exist in the residents of Leminggir Village, Mojosari District, Mojokerto Regency. The focus of this study is to determine the relationship between magic, religion and knowledge with the traditional belief system of society. This descriptive study was prepared using ethnographic methods and the use of J.G Frazer's theory of religious evolution because it is in accordance with the main concepts that discuss magic, religion, and science. The main object of this research is the Kalimati Long Storage. The main data source of this study was obtained based on the results of interviews with Mr. Turoikhan, an elder, a resident of Leminggir Village.The results of the discussion show that there is a belief in the people of Leminggir Village towards magic, religion and knowledge that go hand in hand. As shown by the public's belief in supernatural beings who are the cause of the drowning of children, so that in their search efforts use magic, as well as religious methods as well as the use of technological advances like a motorized boat. The benefit of this research is that it can be used as an educational medium about a culture of tolerance and mutual respect for the existence of various beliefs. Keywords: evolution religi; traditional belief system; Long Storage Kalimati